2016
DOI: 10.1073/pnas.1523266113
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning of degraded speech by minimizing prediction error

Abstract: Human perception is shaped by past experience on multiple timescales. Sudden and dramatic changes in perception occur when prior knowledge or expectations match stimulus content. These immediate effects contrast with the longer-term, more gradual improvements that are characteristic of perceptual learning. Despite extensive investigation of these two experience-dependent phenomena, there is considerable debate about whether they result from common or dissociable neural mechanisms. Here we test single-and dualm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
164
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(200 citation statements)
references
References 89 publications
36
164
0
Order By: Relevance
“…These findings are in line with other work demonstrating cholinergic effects on visual perception and cortical function in AD,8 with retained endogenous perceptual learning mechanisms 15. While the mechanism of the procholinergic effect on degraded speech perception remains undefined, there are several plausible candidates, acting alone or in concert: these include enhanced precision of synaptic transmission and predictive filtering in ascending auditory pathways and facilitation of spectral integration, feature encoding and tracking in auditory cortex 6, 16, 17, 18, 19, 20…”
Section: Discussionsupporting
confidence: 88%
“…These findings are in line with other work demonstrating cholinergic effects on visual perception and cortical function in AD,8 with retained endogenous perceptual learning mechanisms 15. While the mechanism of the procholinergic effect on degraded speech perception remains undefined, there are several plausible candidates, acting alone or in concert: these include enhanced precision of synaptic transmission and predictive filtering in ascending auditory pathways and facilitation of spectral integration, feature encoding and tracking in auditory cortex 6, 16, 17, 18, 19, 20…”
Section: Discussionsupporting
confidence: 88%
“…The intelligibility of the NV sentences was low before training [mean ¼ 26.07%, standard error (SE) ¼ 1.91] and improved after training (mean-¼ 56.34%, SE ¼ 2.59). The intelligibility of untrained 4-band NV sentences also improved (relative to the matched pre-training sentences) after training (mean-¼ 40.50%, SE ¼ 2.10), which suggests that the training could generalize to new speech utterances, in line with previous reports (Davis et al, 2005;Sohoglu and Davis, 2016). Both improvements were significant [pre-vs post-trained: t(23) ¼ 18.34, p < 0.001; prevs post-untrained: t(23) ¼ 10.14, p < 0.001, Bonferroni corrected], but intelligibility after training was stronger for the trained sentences compared to the untrained sentences [t(23) ¼ 10.64, p < 0.001].…”
Section: Training Improved the Intelligibility Of 4-band Nv Speechsupporting
confidence: 89%
“…Crucially, the NV speech sentences were initially poorly intelligible but could be understood after training (Davis et al, 2005;Sohoglu and Davis, 2016). Hence, before and after training, the NV speech would have the same acoustic information but not carry the same linguistic information.…”
Section: Introductionmentioning
confidence: 99%
“…Kraljic et al, 2008b). These findings are reminiscent of Sohoglu and Davis (2016), who found that listeners learned best from partially intelligible (6-channel speech) than from unintelligible (1-channel) or highly intelligible (24-channel) speech. It should be noted that learning of complete remappings has been found in several studies (Sumner, 2011;Weatherholtz, 2015) for different contrasts (bilabial stops; vowels) in different paradigms (exposure to the deviant pronunciations via accent rating; narrative exposure), indicating that future work should tease apart variables responsible for differences across studies.…”
Section: Discussionmentioning
confidence: 64%
“…Our goal here is to assess how the typicality of the pronunciation variant affects perceptual learning. There is already empirical evidence that phonetic variation that deviates considerably from a canonical pronunciation (i.e., with heavily accented items in a nonnative accent, Witteman et al, 2013), that interferes with lexical recognition (i.e., when listeners have lower thresholds in a lexical decision task, Scharenborg & Janse, 2013), or that is less intelligible because of signal degradation (i.e., one-channel speech, Sohoglu & Davis, 2016) does not lead to perceptual learning. Further, Ganong's (1980) finding that listeners' boundaries shift more in accordance with lexical bias at their own perceptual category boundary than at continuum end points suggests different amounts of retuning across degrees of ambiguity.…”
Section: Introductionmentioning
confidence: 99%